2020
DOI: 10.1136/bmj.m3330
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment and suicide

Abstract: Sexual harassment is a serious public health problem and workplace hazard

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Sexual harassment experiences coping also had a direct (unmediated) effect on the organizational, physical, and reproductive health outcomes. Regarding the relationship between SH experience coping and the mentioned outcomes, our study agrees that coping with SH sometimes worsens job, psychological, and health outcomes [80,81]. However, one of the essential findings in our study is the direct effect of sexual harassment coping on reproductive health outcomes, such as menstrual disorders, menstrual symptoms, and transactional sex practices.…”
Section: Discussionsupporting
confidence: 78%
“…Sexual harassment experiences coping also had a direct (unmediated) effect on the organizational, physical, and reproductive health outcomes. Regarding the relationship between SH experience coping and the mentioned outcomes, our study agrees that coping with SH sometimes worsens job, psychological, and health outcomes [80,81]. However, one of the essential findings in our study is the direct effect of sexual harassment coping on reproductive health outcomes, such as menstrual disorders, menstrual symptoms, and transactional sex practices.…”
Section: Discussionsupporting
confidence: 78%
“…One study indicated that the death rate due to suicide after exposure to sexual harassment is equivalent to the death rate due to cancer. Therefore, workplace sexual harassment should be considered both an occupational hazard and a significant public health problem (Sarkar et al, 2020). Organizations worldwide face a critical problem of violence in the workplace, which is embodied in the five types of sexual harassment mentioned above (Cullen et al, 2018;Cheng et al, 2014;Stutzenberger and Fisher, 2014).…”
Section: Introductionmentioning
confidence: 99%